Pelatihan Penerapan Model Ingat Minum Obat TBC Untuk Penderita TBC Di Kelurahan Maccini Sombala Kota Makassar - sinala, santi; Rusli, Rusli (Jurnal Pengabdian Kefarmasian, 2024)
Training On the Implementation of The Tuberculosis Medication Remember Model for Tuberculosis Patients in Maccini Sombala Village, Makassar CityBackground, National Basic Health Research Data in 2018, showed that the prevalence of pulmonary Tuberculosis in South Sulawesi Province was 0.36%, almost equivalent to the national prevalence of 0.42%. In 2020 in Makassar City, the number of patients who recovered was 1,651 people out of 5412 patients treated. This is due to non-compliance in taking medication by TB sufferers, which is caused by the factor of forgetting to take medication and the lack of Medication Supervisors. The aim is to form Medication Supervisors from families or cadres who are equipped with knowledge about the model for remembering to take TB medication with the innovation of medicine boxes or plastic. Method, community service to cadres of Maccini Sombala sub-district, Makassar City in the form of counseling and training in implementing the model of remembering to take medication using plastic medicine boxes that have been given information on the day. To determine the increase in knowledge, pre and post tests were given to the cadres. The results, an increase in cadre knowledge about Tuberculosis treatment management from 35% to 92.5%. This community service activity is an effort to increase compliance in taking medication for Tuberculosis patients so that the prevalence of Tuberculosis disease decreases. Conclusion, there has been an increase in the knowledge of the target audience regarding the ins and outs of Tuberculosis disease and the community has been trained and directed in implementing the model of remembering to take Tuberculosis medicationLatar Belakang, Data Riset Kesehatan Dasar Nasional tahun 2018, menunjukkan bahwa prevalensi TBC paru di Provinsi Sulawesi Selatan 0,36%, hampir setara dengan prevalensi secara nasional yakni 0,42%. Pada tahun 2020 di Kota Makassar, jumlah pasien yang sembuh sebanyak 1.651 orang dari 5412 pasien yang diobati. Hal ini disebabkan karena ketidakpatuhan minum obat oleh penderita TBC, yang diakibatkan oleh factor lupa minum obat dan kurangnya Pengawas Minum Obat (PMO). Tujuan, untuk membentuk PMO yang berasal dari keluarga atau kader yang dibekali dengan pengetahuan tentang model untuk ingat dalam minum obat TBC dengan inovasi kotak atau plastic obat. Metode, pengabdian kepada masyarakat pada kader-kader kelurahan Maccini Sombala, Kota Makassar dalam bentuk penyuluhan dan pelatihan penerapan model ingat minum obat dengan menggunakan kotak plastik obat yang telah diberikan keterangan hari. Untuk menentukan peningkatan pengetahuan, diberikan pre dan post test kepada kader-kader tersebut. Hasil, peningkatan pengetahuan kader tentang tatalaksana pengobatan TBC dari 35% menjadi 92,5%. Kegiatan pengabdian ini menjadi upaya dalam meningkatkan kepatuhan minum obat penderita TBC sehingga prevalensi penyakit TBC semakin berkurang. Kesimpulan, Telah terjadi peningkatan pengetahuan khalayak sasaran mengenai seluk beluk penyakit TBC dan Masyarakat telah dibina dan diarahkan dalam menerapkan model ingat minum obat TBC